Images of Excellence: Plato's Critique of the Arts - Janaway, Christopher (Oxford Oxford University Press, 1995)
The book is an examination of Plato's philosophy of art. Central to the book are Plato's arguments in the Republic that traditionally accepted forms of poetry, drama, and music are of questionable value, on the grounds that they do not arise from knowledge on the part of artists, and that they can be harmful because they appeal to the emotional side of the psyche. The book suggests that Plato has a better case for his views than has often been claimed, given the context of his ethics and epistemology, and that his views challenge much of what is accepted as good art in modern thought. To understand Plato's position, his views on inspiration, craft expertise (techne), beauty, moral education, and representation (mimesis) are examined through the discussion of a number of his early and middleperiod dialogues. It is argued that Plato's later writings do not significantly retract the critical views of the arts found in the Republic. Throughout, links are made with recent philosophical aesthetics, and the question posed is what defence of art modern thinking can or should make against Plato.
Keywords: Plato -- 428/427-348/347 BC; Esthetics